Phylogenetic relationships and biogeography of Psoraleeae (Fabaceae) - Bello, Abubakar; Stirton, Charles H; Chimphango, Samson Bm; Muasya, A Muthama (Botanical journal of the Linnean Society, 2022)
Abstract Psoraleeae consist of c. 228 species in ten genera, distributed worldwide but mostly in the temperate biome. Here, we reconstruct the phylogenetic history of Psoraleeae using eight molecular markers (rpl32-trnL, trnQ-rps16, trnS-trnG, matK, rbcLa, rpoB-trnC, trnL-trnF and ITS) to test the monophyly and previous hypotheses on generic relationships and to reconstruct the biogeographical history (distribution pattern, potential ancestral area and biome). The monophyly of Psoraleeae is supported. The African Otholobium and Psoralea form a strongly supported clade that is sister to the rest of Psoraleeae. However, Otholobium is not monophyletic; the American taxa of the genus are resolved as closer to Bituminaria, whereas Psoralea is a clade derived from within African Otholobium. South African Otholobium is subsumed into Psoralea, the latter having priority, with a synopsis of species level nomenclature provided here. An expanded sampling of Cullen reveals three clades comprising Mediterranean (Cullen americanum), African (Cullen obtusifolium and Cullen biflorum) and Eurasian (Cullen corylifolium and Cullen drupaceum) taxa, whereas Australian Cullen are a derived clade (BS = 95%, PP = 1.00). Biogeographic reconstructions show that Psoraleeae probably originated in the Mediterranean south biome of Africa in the Late Miocene, c. 8.2 Mya, and then dispersed into the succulent biome of the Americas, Mediterranean north biome, temperate grasslands of Africa and Australia to the temperate forest of Eurasia. Climate changes in the Late Miocene, changes induced by ocean currents during the Quaternary and environmental heterogeneity are proposed as the major drivers of speciation in Psoraleeae.